2019
DOI: 10.1016/j.bone.2019.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Senescent and apoptotic osteocytes and aging: Exercise to the rescue?

Abstract: Osteocytes are the most prevalent cell in the skeleton and are the master regulator of bone remodeling. Despite the understanding that osteocytes have a multiyear lifespan, and some factors induce apoptosis in osteocytes, much less is understood about the induction and consequences of osteocyte senescence. Filling these gaps in knowledge will provide novel approaches to slowing age-related bone loss and preventing fragility fractures. The purpose of this review is to examine the roles of senescence and apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…Prevention of the pro-inflammatory secretome of senescent cells in aged mice with a JAK inhibitor improved bone mass and strength (94). It has been hypothesized that exercise to increase mechanical strain on bone could improve the senescent phenotype in aging (95). It remains to been seen whether a lack of mechanical loading and a lack of adequate mechanosensory ability or pro-inflammatory senescent markers occurs first during aging in osteocytes.…”
Section: Mechanosensing and Inflammatory Signalsmentioning
confidence: 99%
“…Prevention of the pro-inflammatory secretome of senescent cells in aged mice with a JAK inhibitor improved bone mass and strength (94). It has been hypothesized that exercise to increase mechanical strain on bone could improve the senescent phenotype in aging (95). It remains to been seen whether a lack of mechanical loading and a lack of adequate mechanosensory ability or pro-inflammatory senescent markers occurs first during aging in osteocytes.…”
Section: Mechanosensing and Inflammatory Signalsmentioning
confidence: 99%
“…Moreover, the LCN was shown to be the main actor in bone mechanical answer to loading 17,18,[23][24][25][26][27] . Indeed, it was recently shown that a significantly higher number of osteocytes was present around immediately loaded human dental implants with respect to control sites left to heal submerged (i.e.…”
mentioning
confidence: 99%
“…Axial ( Z ) apparent modulus of the proximal tibia has been recorded by numerous authors with values ranging from 2.5–3780 MPa which agrees well with our data. [ 5,6,12,17–31 ] It is noted that a number of studies report apparent modulus to be significantly less or greater than our study, which may be due to differences in experimental method, small samples sizes of predominantly young males or inclusion of cortical bone regions within cubes. [ 5,22,30,32,33 ] Studies such as those by Johnston et al, Nazemi et al, and Ashman et al have found apparent modulus from alternative methods (e.g., indentation testing, finite element simulations combined with neural networks or ultrasound testing).…”
Section: Resultsmentioning
confidence: 56%